Effect of Paecilomyces lilacinus on tomato plants and the management of root knot nematodes: Paecilomyces lilacinus on tomato root knot disease (Journal of the Bangladesh Agricultural University, 2019)
Effect of Paecilomyces lilacinus on tomato plant growth and the management of root knot nematodes in tomato was studied. The research work was conducted in Microbiology & Bio-control Laboratory, Department of Plant Pathology, Bangladesh Agricultural University, Mymensingh and in Net-house of Department of Plant Pathology, Bangladesh Agricultural University, Mymensingh, during the period from July, 2016 to October, 2017. In net-house pot culture experiment, four different treatments were used viz., T1: Inoculation of egg masses (10 egg masses/plant) of Nematodes (Meloidogyne spp.), T2: Application of P. lilacinus, T3: Application of egg masses of Nematodes and P. lilacinus simultaneously, and T4: Control (non-treated). Spore suspension (10×105 Conc.) of P. lilacinus was mixed with the soil before transplantation and Meloidogyne spp. was inoculated on three days after transplantation. Application of P. lilacinus in soil enhanced the plant growth parameters of tomato plants. Inoculation of Meloidogyne spp. reduced plant growth and the reduction was increased with the increase of inoculum density of Meloidogyne spp. Maximum plant growth reduction was recorded when Meloidogyne spp. was inoculated alone. The maximum plant growth was recorded in case of application of P. lilacinus to soil. A high percentage (85%) of egg masses of Meloidogyne spp. was infected by P. lilacinus when applied togetherJ. Bangladesh Agril. Univ. 17(1): 9–13, March 2019